Physical activity in Indonesian University students: the contradictory roles of dispositional mindfulness and self-control - Yusainy, C.; Chan, Derwin; Hikmiah, Z.; Anggono, C. (Routledge, 2019)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Physical inactivity is now identified as one of the major risk factors for global mortality, including in Indonesia. Past research in Western settings have demonstrated the efficacy of self-determined or autonomous forms of motivation in predicting health-related behaviours, and that association between these variables could possibly be moderated by individual differences in mindfulness. In terms of mindfulness, individuals from different cultures may vary in their familiarity and acceptance of mindfulness in daily life. Moreover, the ways though which individuals exhibit qualities of mindfulness are often intertwined with their capacity for self-control. In this correlational study utilizing cloud-based online survey, samples of Indonesian undergraduates (N = 411, mean age = 20.202, SD = 1.406) completed self-report measures of trait mindfulness, trait self-control, autonomous motivation, and physical activity. Bootstrap multiple regression analysis indicated that association between autonomous motivation and physical activity is strengthened by trait self-control (p = .017), but conversely, weakened by trait mindfulness (p = .024). Cultural perspective may help explain the dynamics of mindfulness, self-control, autonomous motivation, and physical activity.